2003
DOI: 10.1097/00005176-200311000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density of the Lumbar Spine in Children and Adolescents With Celiac Disease on a Gluten-Free Diet in São Paulo, Brazil

Abstract: The BMD of adolescents with CD was lower than that of the control subjects, whereas no difference was found between the BMD of children with CD and that of control subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 35 publications
3
27
0
3
Order By: Relevance
“…Children with CD have a lower bone mass at diagnosis compared with healthy controls and have revealed complete recovery or significant improvement of BMD following diet therapy (11)(12)(13)(14). In this study, we also observed a lower BMD in celiac patients compared with the healthy subjects.…”
Section: Discussionsupporting
confidence: 68%
“…Children with CD have a lower bone mass at diagnosis compared with healthy controls and have revealed complete recovery or significant improvement of BMD following diet therapy (11)(12)(13)(14). In this study, we also observed a lower BMD in celiac patients compared with the healthy subjects.…”
Section: Discussionsupporting
confidence: 68%
“…It has been suggested that patients with a shorter symptomatic period, recover more completely than those suffering longer periods of untreated CD (Scotta et al, 1997). Sdepanian et al (2003) found that BMD was significantly lower in adolescent with CD on GFD compared with controls but not in children with CD compared with controls; the authors attributed these findings to the longer time between symptoms and diagnosis in adolescents, due to which they suffer more malnutrition and more bone damage than children. In our study, children older than 4 years of age compared with young children suffered a longer period between symptoms and diagnosis.…”
Section: Discussionmentioning
confidence: 97%
“…In São Paulo, Brazil, SDEPANIAN et al (58) , in 13 adolescents with CD reported that BMD was lower than that of the controls. Furthemore, the proportion of adolescents who had started a GFD after 2 years of age was higher than that of children with CD, an experience similar to ours.…”
Section: Bone Diseasementioning
confidence: 95%